Acoustic Strength of Green Turtle and Fish Based on FFT Analysis - Azrul, Mahfurdz; Sunardi, S.; Hamzah, Ahmad; Syed Abdullah, Syed Abdul Kadir; Nazuki, Sulong (The Science and Information (SAI) Organization Limited, 2013)
the acoustic power at difference angle and distance were measure for four different ages of Green Turtles and three species of fish using modified echo sounder V1082. The echo signal from TVG output was digitized at a sampling rate 1MHz using analog to digital converter (Measurement Computing USB1208HS). Animals were tied with wood frame to ensure it can’t move away from the sound beam. The scatter value for fish demonstrates echo strength is different and depends on the angle of measurement. The lowest acoustic power of fish was recorded from their tail. The finding show that, there is significant difference between fish and turtles aged 12 to 18 years at 4.5 meter and 5 meter. The carapace and plastron of sea turtle gives high backscattering strength compare to other side. The high value obtained probably because of the hard surface of the carapace and plastron. This result is considered important in determining the best method of separating sea turtle and fish. Through this result, revealed that size, surface and animal angle play important role in determining acoustic strength value.